The prevalence of multiple sclerosis in Sicily. I: Monreale city. Issue 2 (June 1981) - Savettieri, G; Daricello, B; Giordano, D; Karhausen, L; Dean, G
Abstract : The prevalence of probable multiple sclerosis in Monreale city, close to the university city of Palermo, Sicily, is at least 43 per 100 000. If the possible multiple sclerosis patient is included, it is 47 per 100 000. This prevalence is not significantly different from that found in Enna city, 53 per 100 000. The prevalence in Sicily and, no doubt, in Italy has, in the past, been seriously underestimated. This confirms the need for thorough studies of small populations if many patients are not to be overlooked in a prevalence survey.